2012
DOI: 10.4102/jsava.v83i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Technique for the collection of clear urine from the Nile crocodile (<i>Crocodylus niloticus</i>)

Abstract: Urine samples can be a very useful diagnostic tool for the evaluation of animal health. In this article, a simple technique to collect urine from the Nile crocodile (Crocodylus niloticus) was described, based on a similar unpublished technique developed for the American alligator (Alligator mississippiensis) using a canine urinary catheter. With this technique, it was possible to collect relatively clean urine samples from Nile crocodiles of different sizes using canine urinary catheters or small diameter st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…This pattern of antibiotic usage is similar to that reported in Orissa, India by Sahoo et al ( 2010 ), where the beta-lactams, fluoroquinolones and tetracyclines were the most commonly used antibiotics in dairy cattle and poultry. Similarly, a survey conducted in South Africa to determine antibiotic usage in food animals showed that tetracyclines and beta-lactams were amongst the first four leading antibiotics commonly used in the country (Eagar, Swan & Van Vuuren 2012 ). This finding is also corroborated by a report from Tanzania (Katakweba et al 2012 ), which indicated that the tetracyclines and beta-lactams/aminoglycosides were the foremost antibiotics used in livestock in the area.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of antibiotic usage is similar to that reported in Orissa, India by Sahoo et al ( 2010 ), where the beta-lactams, fluoroquinolones and tetracyclines were the most commonly used antibiotics in dairy cattle and poultry. Similarly, a survey conducted in South Africa to determine antibiotic usage in food animals showed that tetracyclines and beta-lactams were amongst the first four leading antibiotics commonly used in the country (Eagar, Swan & Van Vuuren 2012 ). This finding is also corroborated by a report from Tanzania (Katakweba et al 2012 ), which indicated that the tetracyclines and beta-lactams/aminoglycosides were the foremost antibiotics used in livestock in the area.…”
Section: Discussionmentioning
confidence: 99%
“…In the Nile crocodile, faeces and urine are stored in different parts of the cloaca, namely the rectum and urinary chamber, preventing a mix of defaecated urine and faecal material under normal circumstances (Myburgh et al 2012). The enclosures were inspected three times a day (in the morning, at noon, and in the afternoon), all faeces collected, immediately frozen at -20°C, and kept frozen until hormone analysis.…”
mentioning
confidence: 99%
“…Once the distal end of the phallus reaches the level of the vaginal openings and the glans inflates, the expanded glans ridge would fill the most proximal lumen of the female proctodeum and be distally bounded by the uroproctodeal fold (Figure 13b), as proposed by Johnston et al, 2014 in Crocodylus porosus . This sphincter is sufficiently resilient and contractible for crocodylians to retain urine in the urodeum (Myburgh et al, 2012). Therefore, female uroproctodeal fold contraction could limit intromission beyond this point.…”
Section: Discussionmentioning
confidence: 99%